LIMPING ON TWO LEGS: UYGHUR DIASPORA ORGANIZATIONS AND THE PROSPECTS FOR EASTERN TURKESTAN INDEPENDENCE - SHICHOR, Yitzhak (CENTRAL ASIA AND THE CAUCASUS, 2007)
Walking on two legs” (liangtiaotuizoulu), that is trying to promote two policies, often contradictory, at the same time, is a Chinese political term and as such may not be very popular among Uyghurs. Nonetheless, it is the best expression I can use to define the current state of the Eastern Turkestan independence movement—in a positive, rather than a negative sense. Apparently, this expression denotes a split or a break. Indeed, the Uyghur Diaspora has been divided into a number of organizations and associations that have been established throughout the years, especially since the early 1990s. They held a number of congresses and other meetings and managed to place the issue of Eastern Turkestan independence on the international agenda using advanced communications media, petitions and demonstrations and personal activism. Yet, their actual success has been quite limited primarily—but by no means only—due to repeated splits and internal rivalries. Attempts to create a universal, acceptable, representative and powerful organization that would provide an umbrella for all the other particular associations and that would have an international impact and a recognized world leader (similar to the Dalai Lama), had by and large failed. This situation was supposed to have changed in April 2004 when a new umbrella organization called the World Uyghur Congress was formed. It was meant to unite the different Uyghur communities and associations all over the world under one unified, recognized and acceptable leadership, something the movement lacked after the death of its lifelong Isa Yusuf Alptekin in 1995, if not before. Just a few months later, however, in September 2004, another umbrella organization emerged in Washington: the Republic of East Turkistan Government in Exile. Since then, the Eastern Turkestan nationalist movement has been “walking on two legs,” and perhaps more—since not all Uyghur associations throughout the world joined either of these new organizations. Moreover, during my meetings with expatriate Uyghurs in 2004-2005 I could sense the tension between the followers of these two “headquarters” that seemingly opted for two different solutions in addressing the Eastern Turkestan independence problem. While the former is ready to compromise and settle for democracy and self-determination (explicitly) and increased autonomy (implicitly), the latter would not accept anything less than complete independence. This bifurcation has again reminded me of another typical Chinese term, “struggle between two lines” (liangtiao luxian douzheng) such as “right” and “wrong,” “correct” and “incorrect,” “advanced” and “backward.” Is this ideological, political and organizational split harmful for the Eastern Turkestan nationalist cause, as many believe? Are these two organizations mutually exclusive? Is one solution better than the other in promoting the Uyghur nationalist cause? In this article, after providing some background, I try to answer these questions and to introduce an outsider’s perspective on the prospects of the two-headed Uyghur nationalist movement based on a provisional analysis and compared, in a preliminary way, to other national liberation movements